Influence of the Use of Tattoos on the Perception of Economic Compensation, A Variable Under the Halo Effect - Rodriguez Fandiño, Juan Camilo (Consorcio de Universidades Mexicanas A.C., 2022)
The halo effect influences decision-making by attributing specific characteristics to events, objects or people, demonstrating that some decisions are not 100% rational as they involve cognitive shortcuts that may or may not be real. The objective of this study was to observe if a particular trait (use of tattoos) can modify the economic perception that a person has about another person, examine the role that sex plays against this trait, and how these factors interact. For this investigation, four photos were used, a man and a woman with and without tattoos; 208 college students were asked to give financial attribution to the submitted photo. Finding higher economic ranges in the photo of men with or without tattoos and a better salary range in women with tattoos. Concluding that indeed a specific characteristic such as a tattoo can change the perception of others against the salary attribution of a person.